Current patterns of care at adult emergency department in Ethiopian tertiary university hospital - Kibur Tarkie; Kassaye Demeke Altaye; Yophtahe Woldegerima Berhe (International Journal of Emergency Medicine, 2023)
Abstract Background The complexity and demands of emergency healthcare service are continuously increasing, and it is important to regularly track the patterns of care at the emergency department (ED). Methodology A retrospective study was conducted at the ED of the University of Gondar Comprehensive Specialized Hospital (UoGCSH) from April 1 to June 30, 2021. Ethical approval was obtained from the Emergency and Critical Care Directorate of UoGCSH. Data was collected from the emergency registry and descriptive analysis was performed. Results A total of 5232 patients have visited and triaged at the ED. All patients who visited the ED have received triage service within 5 min of arrival. The average length of stay at the ED was 3 days. About 79.1% of patients have stayed at the ED beyond 24 h, and the unavailability of beds at admission areas was responsible for 62% of delays. Mortality rate at the ED was 1.4%, and male to female ratio of death was 1.2 to 1. Shock (all types combined), pneumonia with/without COVID-19, and poisoning were the leading causes of death at the ED which were responsible for 32.5%, 15.5%, and 12.7% of deaths respectively. Conclusions Triage has been done within the recommended time after patient arrival. However, many patients were staying at the ED for an unacceptably prolonged time. Unavailability of beds at the admission areas, waiting long for senior clinicians’ decisions, delays in investigation results, and lack of medical equipment were the causes of delayed discharge from the ED. Shock, pneumonia, and poisoning were the leading causes of death. Healthcare administrators should address the lack of medical resources, and clinicians should provide timely clinical decision and investigation results.